Assessing safety analysis at FKM's laboratory (general machine lab) University Malaysia Pahang by using energy analysis method - Suyani, Arifin (2008)
Safety analysis by using energy analysis method has been applied to laboratory Mechanical Engineering Faculty (FKM) of Universiti Malaysia Pahang. This analysis was applied on FKM 3A in FKM’s laboratory which consist general machine such as universal milling machine and conventional lathe machine. The purpose of this analysis is to identify and evaluate hazard occurs at FKM’s Laboratory by applying energy analysis. The approach to this study based on energy concept and straightforward method called Energy Analysis. This method is suitable for obtaining a quick overview of existing hazard. The methods are described step-by-step to show how analysis is practically done. The energy analysis methods for safety analysis seem to have been efficient in identifying hazards occurs at FKM 3A laboratory. The hazard was identified by survey, observation and interview that have been done. By analyzing the identified hazard, safety measure has been proposed. The suggestion also was proposed to improve the safety at the workplace.